UPACARA ADAT OROM SASADU PADA MASYARAKAT DESA WORAT-WORAT KECAMATAN SAHU KABUPATEN HALMAHERA BARAT - Maryo Gilberth Tobo Ngama (HOLISTIK, Journal of Social and Culture, 2024)
Indonesia's multicultural society is spread in various ethnic groups that inhabit the entire archipelago with diverse ethnicities, races, and religions. This variety of tribes inhabits islands scattered throughout the archipelago, making this country has a variety of cultures that each community group each has traditions and customs that continue to be preserved. One of the people who still maintains the traditions and rituals of their ancestors is the Sahu tribe community in Worat-Worat Village. The Sahu tribe has a unique tradition in their culture, namely the ceremony of eating together or in the local language called it the traditional ceremony of Orom Sasadu, which is a tradition passed down from generation to generation by ancestors to be grateful for the harvest they experience in one year. The Orom Sasadu traditional ceremony is a traditional ritual of the Sahu tribe community in general and the people of Worat-Worat Village in particular. The traditional ceremony of Orom Sasadu is a traditional ceremony that has been carried out by the ancestors of the Sahu tribe community in Worat-Worat Village. The traditional ceremony of Orom Sasadu in the previous decade with the current one is different. Concretely in the current era, the celebration of Orom Sasadu is carried out differently from the past, in the past Orom Sasadu was held at the time after the rice harvest as a thanksgiving for the harvest and in the present the community in Worat-Worat Village can be seen from the performance where the source of food served in traditional ceremonies is no longer from the community's rice harvest. Keywords: tradition, traditional ceremony, orom sasadu